Developing a Land Suitability Index for Agricultural uses in Dry Lands from Geologic Point of View Using GIS - a Case Study from Jordan - Al Farajat, Mohammmad; Mohammad, Alsharifa Hind; Diabat, Abdullah; Al Ibraheem, Hassan (Geological Agency, 2015)
DOI:10.17014/ijog.2.2.63-76In the context of the study, a Multi-criteria evaluation (MCE) in GIS was used in developing suitability index to optimize suitable lands for agricultural uses and seasonal farming in dry lands from geologic point of view. This study was performed in the areas between Mafraq and Zarqa Cities in Jordan which are classified as arid lands. The study aims at protecting groundwater from pollution, reducing soil salting, reducing irrigation water loss caused by evaporation, and increasing crop productivity. The geo-environmental parameters of the named area including geology, groundwater depths, soil depths and textures, climatic conditions, topographic settings, and groundwater vulnerability conditions were mapped and converted into layers with special rates, given weights, and then modeled using the multi criteria evaluation (MCE) option, using Decision Making Modeling in IDRISI (GIS software) to reach at the best choice of lands for agricultural activities, and also to determine which of these lands are suitable for summer farming and which are suitable for winter farming.